MAINTENANCE STRATEGY FOR PUBLIC SERVICE BUILDING - Annisa Kesuma Pertiwi (Jurnal Teknologi Berkelanjutan, 2015)
Building maintenance management in the Bandarmasih Passenger Terminal of PT. Pelabuhan Indonesia III (Persero) Branch of Banjarmasin has not been using priority scale method or middle-term maintenance for handling damages, This is due to the fact that the database of building condition is not available. This study aims to create middle-term maintenance strategy plan and prioritise the handling of the building maintenance.Inventory results showed that there were 95 types of work. Based on the analysis of the assessment criteria there were 78 types of work that met the assessment criteria, using SWOT analysis, this number was reduced to 74. Meanwhile, to determine the order of priority of building maintenance the use of MCDM analysis was required.The strategic plans were divided into medium-term strategic plan for 5 years and short-term strategic plan for every year. In 2015 there were 14 types of works determined with an allocation of IDR 502,036,400. In 2016 there were 15 types of works determined with an allocation of IDR 557,611,829. In 2017 there were 11 types of works determined with an allocation of IDR 619,339,459. In 2018 there were 16 types of works determined with an allocation of IDR 687,900,337. In 2019 there were 18 types of works determined with an allocation of IDR 764,050,904. All maintenance works were expected to be completed in 5 years.The strategic plan that has been arranged can be used as preliminary guidelines for building maintenance projects that experience changes in its arrangement of specified list.